WT1-dependent sulfatase expression maintains the normal glomerular filtration barrier - Schumacher, Valerie A.; Schlötzer-Schrehardt, Ursula; Karumanchi, S. Ananth; Shi, Xiaofeng; Zaia, Joseph; Jeruschke, Stefanie; Zhang, Dongsheng; Pavenstaedt, Hermann; Drenckhan, Astrid; Amann, Kerstin Ute; Ng, Carrie; Hartwig, Sunny; et al. (Journal of the American Society of Nephrology, 2011)
Paracrine signaling between podocytes and glomerular endothelial cells through vascular endothelial growth factor A (VEGFA) maintains a functional glomerular filtration barrier. Heparan sulfate proteoglycans (HSPGs), located on the cell surface or in the extracellular matrix, bind signaling molecules such as VEGFA and affect their local concentrations, but whether modulation of these moieties promotes normal crosstalk between podocytes and endothelial cells is unknown. Here, we found that the transcription factor Wilms' Tumor 1 (WT1) modulates VEGFA and FGF2 signaling by increasing the expression of the 6-O-endosulfatases Sulf1 and Sulf2, which remodel the heparan sulfate 6-O-sulfation pattern in the extracellular matrix. Mice deficient in both Sulf1 and Sulf2 developed age-dependent proteinuria as a result of ultrastructural abnormalities in podocytes and endothelial cells, a phenotype similar to that observed in children with WT1 mutations and in Wt1(+/-) mice. These kidney defects associated with a decreased distribution of VEGFA in the glomerular basement membrane and on endothelial cells. Collectively, these data suggest that WT1-dependent sulfatase expression plays a critical role in maintaining the glomerular filtration barrier by modulating the bioavailability of growth factors, thereby promoting normal crosstalk between podocytes and endothelial cell
EVALuna2:21045